Bromo-substituted blocked hexamethylene diisocyanate adduct: synthesis, characterization and application toward polyurethane coating. Issue 5 (9th April 2021) - Jana, Sourita; Ramar, Periyamuthu; Samanta, Debasis; Jaisankar, Sellamuthu N.
Abstract: Hexamethylene diisocyanate (HMDI) reacts with 4-bromo-1 H -pyrazole as a blocking agent to form blocked adducts of isocyanates. The adducts were characterized by FTIR, NMR, thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). In the FTIR spectra, disappearance of a peak at 2250–2270 cm −1 is the indication of blocking of diisocyanate molecule with 4-bromo-1 H -pyrazole blocking agent. The DSC thermogram shows that at 185 °C, the blocked adduct de-blocks and HMDI and blocking agent 4-bromo-1 H -pyrazole has been regenerated. At 185 °C, regenerated HMDI reacts with polyols of different molecular weights to form polyurethane. The polyurethanes were characterized by FTIR, NMR, DSC, TGA and contact angle measurements. These are useful for hydrophilic coating. Graphical abstract: